DAMPAK KJA TERHADAP STRUKTUR KOMUNITAS DIATOM DAN KONDISI KUALITAS PERAIRAN DI WADUK PLTA KOTO PANJANG KABUPATEN KAMPAR - Reatra Ari Koswara; Thamrin Thamrin; Sofyan Husine Siregar (Jurnal Ilmu Lingkungan, 2015)
This study was carried out around. The floating net cages in Koto Panjang HydropowerReservoir from May until June 2014, with the purpose of research is to analyze theinfluence of floating net cages on diatom community structure around the floating netcages, to analyze the condition of aquatic quality around the floating net cages, basedon parameters, physics, chemistry and examine the connection between aquatic qualityand diatom community structure around the floating net cages, based on parameters,physics, chemistry and examine the connection between aquatic quality and diatomcommunity structure around the floating net cages. The method which was used issurvey method. The analysis and identification was done in Ecology Laboratory andManagement of Aquatic Environment in Marine and Fisheries Faculty of RiauUniversity. The result showed that the variety and abundance of planktonic andperiphytic diatoms are 19 genus with the total of planktonic diatom abundance is 9667cell/L periphytic diatom is 8000 cell/cm2, from the index value of diversity types ofplanktonic diatom (H’) (2,0702 – 2,3446) dominance index value (C) (0,2370 – 0,3125)and uniformity index value (E) (0,7374 – 0,8352), whereas for periphytic diatom, theindex value of diversity types is (0,9950-2,2443), dominance index value is (0,2470-0,5035) and uniformity index value is (0,8682-0,9950). The result of water qualitymeasurement of nitrate is under the recommended threshol as according to GovernmentRegulation Number 82 of 2001 About the Management of Water Quality and Control ofWater Pollution. Based on analysis of variance (ANOVA), it is found that there is verysubstanstial connection among nitrate, phosphate, brightness, temperature and DO onthe diatom community structure. Therefore, there is influence of floating net cages ondiatom community structure and aquatic quality in the area around Koto Panjanghydropower reservoir.